2001
DOI: 10.1590/s0100-879x2001001200009
|View full text |Cite
|
Sign up to set email alerts
|

Plasma insulin levels are increased by sertraline in rats under oral glucose overload

Abstract: Recognition and control of depression symptoms are important to increase patient compliance with treatment and to improve the quality of life of diabetic patients. Clinical studies indicate that selective serotonin reuptake inhibitors (SSRI) are better antidepressants for diabetic patients than other drugs. However, preclinical trials have demonstrated that not all SSRI reduce plasma glucose levels. In fact, fluoxetine increases and sertraline decreases glycemia in diabetic and non-diabetic rats. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Evidence of insulin-dependent hypoglycemic effect of serotonin (Yamada et al, 1989;Sugimoto et al, 1990), SSRIs, or monoamine oxidase inhibitors (Lundquist et al, 1971;Furman, 1974;Smith and Pogson, 1977;Wilson and Furman, 1982;Gomez et al, 2001;Pollak et al, 2001) has been provided in many previous studies. Not all of the SSRIs lowered the plasma glucose in association with the increase of plasma insulin level (Erenmemisoglu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of insulin-dependent hypoglycemic effect of serotonin (Yamada et al, 1989;Sugimoto et al, 1990), SSRIs, or monoamine oxidase inhibitors (Lundquist et al, 1971;Furman, 1974;Smith and Pogson, 1977;Wilson and Furman, 1982;Gomez et al, 2001;Pollak et al, 2001) has been provided in many previous studies. Not all of the SSRIs lowered the plasma glucose in association with the increase of plasma insulin level (Erenmemisoglu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The hypoglycemic activities of these substances are enhanced in mice pretreated with monoamine oxidase inhibitor (Lundquist et al, 1971;Furman, 1974;Smith and Pogson, 1977;Wilson and Furman, 1982). The selective 5-HT reuptake inhibitors (SSRIs, such as fluoxetine and sertraline) can reduce plasma glucose, while the plasma level of insulin was found to be increased (Yamada et al, 1989;Gomez et al, 2001) or to be unaltered (Erenmemisoglu et al, 1999). The exact mechanism by which SSRI or 5-HT agonists mediate hypoglycemic effect remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is more difficult to find information regarding those adolescents who have been diagnosed with Type 2 diabetes, which has recently become an increasing phenomenon. Fortunately, there are accepted therapies for the treatment of depression in patients with diabetes (Gomez et al, 2001;Kassiou & Tsamasiros, 1999;Katon et al, 2003;Lloyd & Brown, 2002). There is a continued need for more practitioners who are informed in both medical and psychiatric treatments so that appropriate referrals can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Sawka, Burgart and Zimmerman (2001) found that some antidepressant medications have been associated with lack of hypoglycemia awareness. Selective Serotonin Reuptake Inhibitors (SSRIs) have been shown to be better antidepressant choices than tricyclic antidepressants for diabetic patients (Gomez, Huber, Lhullier, & Barros, 2001). Tricyclic antidepressants can increase appetite leading to decreased blood glucose control (Jacobson, 1996).…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Nevertheless, TCA, SSRI and AED are only mainly useful in relieving the pain of neuropathy 9,10 . Sertaline, amitriptyline and anticonvulsant drugs are used in the treatment of diabetic neuropathy but they all have side effects.…”
mentioning
confidence: 99%